(untitled) (Global Journal of Human-Social Science, 2011)
The advertisement messages of some products services ideas or organisations are phrases dependent clauses or sentence fragments Some are sentences that are syntactically orthographically and semantically complete The advertisement Messages that are complete sentences however have different constituent patterns This paper presents the constituent patterns of some 140 complete simple-sentence advertisement messages identified among some carefully selected 250 advertisement messages Eighty-five 85 out of the one hundred and forty 140 complete simple-sentence advertisement messages i e 61 have the basic simple sentence patterns Four 4 complete simple-sentence advertisement messages i e three percent 3 have expanded basic sentence patterns making a total of eighty-nine 89 advertisement messages i e sixty-four percent 64 with both the basic and modified basic simple sentence patterns Fifty-one 51 of the whole one hundred and forty 140 complete simple-sentence advertisement messages i e thirty-six percent 36 are those with the non-basic simple-sentence patterns